2020
DOI: 10.3390/ijerph17134778
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Psychological Well-Being and Psychosocial Factors in University Students

Abstract: Determining what factors influence the psychological well-being of undergraduate university students may provide valuable information to inform the development of intervention programs and targeted learning activities. The objective of this study was to investigate the correlation between psychological well-being in university students and their self-reported learning styles and methodologies, social skills, emotional intelligence, anxiety, empathy and self-concept. The final sample consisted of 149 Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
0
15

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 55 publications
5
55
0
15
Order By: Relevance
“…In our study, potentially enjoying relationships and being more intentional about how time is spent may make participants feel less lonely, have a greater sense of agency and control, and serve as a buffer to satisfy the need for certainty. Also, other research on coping during the COVID-19 pandemic has shown that, for example, autonomy and purpose in life predict PWB [ 97 ] and pursuing hobbies and staying outdoors were predictors of fewer depressive symptoms [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, potentially enjoying relationships and being more intentional about how time is spent may make participants feel less lonely, have a greater sense of agency and control, and serve as a buffer to satisfy the need for certainty. Also, other research on coping during the COVID-19 pandemic has shown that, for example, autonomy and purpose in life predict PWB [ 97 ] and pursuing hobbies and staying outdoors were predictors of fewer depressive symptoms [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that the physical self-concept is positively related with happiness and well-being. Fox [ 9 , 10 ] identified that self-perception of body is essential for mental health and well-being, and Morales-Rodríguez and colleagues [ 11 ] reported that physical self-concept is one of the psychosocial factors of the psychological well-being in university students. Roh [ 12 ] assured that the perception of one’s physical state is correlated with health perception and psychological well-being, and Kim and Oh [ 13 ] also reported by a meta-analysis that there was a positive correlation between physical self-perception and happiness.…”
Section: Introductionmentioning
confidence: 99%
“…It is considered fundamental that these two constructs are positive among their dimensions, since high levels of self-concept allow an awareness of oneself and of the perceptions about different aspects that converge in the personal and social process of the individual, it will motivate the promotion and treatment of an adequate psychosocial adjustment, where the perception, management and use of emotions result in skills and abilities related to psychological well-being [ 15 ]. These positive relationships are the object of study in various research projects, where the idea that having a positive perception of oneself, as well as feeling valid and capable, allows for the creation of a more favourable scenario to develop adequately in various areas [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%